2017
DOI: 10.4172/2169-0316.1000212
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of TQM and JIT For Basic Metal Industries Global Competitiveness

Abstract: The purpose of this study is to develop an integrated continuous improvement model so as to improving the global competitiveness of basic metal industries. The study concerned on the Ethiopian basic metal-manufacturing firms, with a special emphasis on the medium and large manufacturing industries. However, basic metal industries occupy a prominent position in the development agenda of many developing countries like Ethiopia. Hence, this study investigated the role of continuous improvement for global competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Similarly, both Getachew et al (2017) and Dametew et al (2017) have developed a conceptual integrated model of TQM and JIT practices with the context of Ethiopian printing and basic metal industries respectively. The first study assessed the global competitiveness of Ethiopian economy and analyzed the current trends of CI tools implementation for global competitiveness of basic metal industries.…”
Section: Existing Integrated Kaizen Philosophy Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, both Getachew et al (2017) and Dametew et al (2017) have developed a conceptual integrated model of TQM and JIT practices with the context of Ethiopian printing and basic metal industries respectively. The first study assessed the global competitiveness of Ethiopian economy and analyzed the current trends of CI tools implementation for global competitiveness of basic metal industries.…”
Section: Existing Integrated Kaizen Philosophy Frameworkmentioning
confidence: 99%
“…Thus, this research will provide an associated result by identifying the most widely found practices of the stated CI programs in literatures. For this case, these most extensively quoted practices of the programs can be divided into unique techniques or practices to all programs separately, and drivers (or social and technical factors or common practices or CSFs) to all the programs as used in (Lopes et al, 2022;Sisay et al, 2021;Dametew et al, 2020;Sahoo and Yadav, 2020;Tilahun et al, 2020;Phan et al, 2019;Hailu et al, 2018a;Masudin and Kamara, 2018;Khamkham, 2017;Tesfaye and Kitaw, 2017;Getachew et al, 2017;Dametew et al, 2017;Nandurkar et al, 2014;Cua et al, 2001).…”
Section: Existing Integrated Kaizen Philosophy Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…All the same, several African countries with large textile sectors are also recovering from an unfavourable change in international trade policies (Gabriel Negatu, 2014). In particular, most eastern parts of Africa, manufacturing sectors can have a limited role in GDP and employment creation in the regions (Damtew et al,2017and Georgise et al, 2014b. Manufacturing performance and competitiveness, for example, account for a relatively small share of GDP in the study countries (ranging from 3.8% to 11%) compared to levels of manufacturing typically associated with industrializing countries (30% to 40%) (Gabriel Negatu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, Ethiopian textile industries have faced a variety of challenges, including a lack of competitiveness at both the local and global levels, as well as a lack of pro tability (Tadesse, 2017). Also, fragmental and nonintegrated supply chain processes on local manufacturing industries, including Ethiopia's textile and apparel industries, heavily depend on imported raw materials and semi-nished textile and apparel products (Damtew, 2022, Damtew et al, 2017. The textile sector's supply chain, starting from the cotton farm to the nal customer, both in the local and foreign market, is full of challenges.…”
Section: Introductionmentioning
confidence: 99%